Bibliometric Analysis of European Research on Digital Divide: An Exploration of the Corporate Landscape - Luis Carlos Castillo-Tellez (International Telecommunications Society (ITS), 2023)
This research provides an exhaustive analysis of the European digital divide literature's evolution and current state, particularly emphasizing the often-underexplored corporate sector. The digital divide, denoting disparities in digital access, literacy, and fluency, has become a critical concern in the era of rapid digital transformation. Despite its significance, research on the corporate digital divide is limited. This study aims to address this gap to advance in different research avenues on digital disparities in the business realm. Using a dataset of 1609 documents published from 2000 to 2022, extracted from Web of Science, Scopus, and Dimensions, the study employs three bibliometric techniques-performance analysis, science mapping, and network analysis-to examine the research landscape, including scientific output, impact, and intellectual structure within the field. The research uncovers key trends and shifts in European digital divide research across three distinct periods (2000- 2007, 2008-2015, 2016-2022). It highlights the evolution of research themes from access inequalities to a nuanced understanding of skills and usage disparities, reflecting the multifaceted nature of the digital divide. The study reveals a significant gap in the literature regarding the corporate digital divide, with only 30 out of the 1609 documents directly addressing this area. It further identifies leading institutions, publications, and thematic clusters in digital divide research, emphasizing the role of intellectual interactions and thematic connections in shaping the field.
Keywords: 330; Digital Divide; Bibliometric Analysis; European Research; Corporate Digital Divide; Digital Divide Evolution